Adopsi International Financial Reporting Standard untuk Usaha Mikro, Kecil, dan Menangah - Anisah, Astri Lutfiatul; Widiyati, Dian (Journal of Law, Administration, and Social Science, 2025)
This paper aims to analyze the factors influencing the adoption of IFRS for SMEs from a cross-country perspective. The research method used in this study is qualitative, with a scoping review approach. The data employed in this study is secondary data in the form of journal articles published on Google Scholar (https://scholar.google.com/) and Emerald Insight (https://www.emerald.com/) within the period of 2020 to 2024. The scoping review includes mapping studies on the adoption of IFRS for SMEs across countries. The study concludes that the adoption of IFRS for SMEs in different countries is influenced by factors such as needs and relevance, institutional pressures, environmental and cultural aspects, standard complexities, user perceptions, adaptive approaches, regulatory frameworks and government support. The factors affecting IFRS for SMEs adoption vary between countries; however, the fundamental principle of implementing this standard lies in creating a consistent, credible, and internationally acceptable financial reporting system. Future research is expected to consider other factors not covered in this study to provide a more comprehensive contribution to the understanding and development of IFRS for SMEs adoption at a global level.